Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

A Bayesian robust framework for estimating residential PM2.5 infiltration and indoor–outdoor contributions using paired low-cost sensors - Keqin Yang; Wenbin Zhuang; Rui You; Louise B. Weschler; Shu Wang; Charles J. Weschler; Jingya Wei; Ningrui Liu; Yinping Zhang (Building and Environment, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

MS-R outperforms RGB: Lightweight CYOLO-BiCNet enables efficient detection and storage optimization of cotton flowers - Mian Chen; Kai Ma; Xiaoli Geng; Daowu Hu; ShuaiPeng Fei; Shoupu He; Xiongming Du; Meiyan Shu; Shunfu Xiao; Rui Zhang; Yuntao Ma (Precision Agriculture, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

East Lake evolution and prehistoric human activity response to Holocene monsoon hydroclimate in the Middle Yangtze Valley - Hongye Liu; Yansheng Gu; Yuenan Li; Rui Zhang; Junwu Shu; Min Zheng; Weizhe Chen; Shaofan Fang; Zongmin Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Numerical manifold method for compression molding of granular materials - Xuezhen Zhai; Yuchen Guo; Yongjia Zhang; Rui Yue; Liuchen Shu; Youjun Ning; Pengwan Chen; Ge Kang (Computers and Geotechnics, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

CTF-TL: Coarse-to-Fine temporal localization framework for precise recognition of posture transition behaviors in periparturient sows - Zikang Chen; Yan Luo; Chao Yuan; Kai Yan; Rui Diao; Jiachao Zhang; Mingxia Shen; Xiangbo Shu; Xingjian Gu; Mingzhou Lu (Computers and Electronics in Agriculture, 2026)

Machine-learning-guided risk stratification of bacterial contamination in food powered by a dual-mode lateral flow biosensor using low-crystallinity nanozyme labels - Rui Shu; Sijie Liu; Huilin Jia; Lei zhao; Ibrahim A. Darwish; Jianlong Wang; Daohong Zhang (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Hidden acidification beneath soil-covered mine waste dumps: links to oxygen-limited sulfur oxidation - Ziyi Li; Zhengbo Yue; Junyi Gu; Shu Wang; Lu Zhang; Zijie Yu; Rui Deng; Jin Wang (Journal of Environmental Management, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Butyrate-induced trained immunity enhances bacterial killing ability of head kidney macrophages in turbot (Scophthalmus maximus L.) - Shu Zhao; Jinjin Zhang; Wentao Wang; Shufei Liang; Mengqi Chen; Rui Shao; Xinmeng Liao; Qinghui Ai; Kangsen Mai; Min Wan (Fish & Shellfish Immunology, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Cottonseed protein as a sustainable alternative plant protein: Basic characteristics, recent advancements, applications and limitations - Xinjie Shang; Shu Li; Shiyu Lin; Shihao Sun; Li Liang; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Uncovering cryoprotective mechanism of natural deep eutectic solvents for highly efficient cryopreservation of Lactiplantibacillus plantarum - You Tian; Da-Wen Sun; Shu-Ti Zhang; Rui Hu; Zhiwei Zhu (Food Chemistry, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Immunomodulatory Effects of Angelica Sinensis Polysaccharides on Juvenile Chinese Sturgeon (Acipenser sinensis): Physiological and Molecular Insights - Jianming Zhang; Tian Tian; Dezhi Zhang; Rui He; Debin Shu; Wei Jiang; Yacheng Hu (Fishes, 2025)
The Chinese sturgeon (Acipenser sinensis) is a critically endangered species with significant ecological and economic value. This study investigates the effects of Angelica sinensis polysaccharides (ASPs) on the antioxidant and immune responses of juvenile Chinese sturgeon through physiological and molecular approaches. Healthy juvenile Chinese sturgeon (n = 120, mean body weight 356.50 ± 92.87 g) were fed diets supplemented with 0%, 0.5%, 1.0%, and 2.0% ASP for 36 days. Results showed that ASP, particularly at 2.0%, significantly enhanced serum antioxidant capacity by increasing activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and reduced malondialdehyde (MDA) content. Immune indices, including immunoglobulins (IgG and IgM), complement components (C3 and C4), lysozyme (LSZ) activity, and antimicrobial peptides (AMPs), were also significantly elevated in the 1.0% and 2.0% ASP groups. Transcriptome sequencing of spleen and kidney tissues from the control and 2.0% ASP groups identified 151 and 467 differentially expressed genes (DEGs), respectively, with significant enrichment in immune-related pathways such as phagocytosis and the MAPK signaling pathway. Ten candidate immune-related genes (e.g., PDIA4, H-2Q9α, TTC39B) were validated by qRT-PCR, confirming the reliability of the RNA-seq data. This study demonstrates that ASP can enhance the antioxidant and immune responses of juvenile Chinese sturgeon, providing a potential natural immunostimulant for aquaculture. These findings offer a scientific basis for the conservation and sustainable production of this endangered species and highlight the need for further research on the application of ASP in sturgeon aquaculture.

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

Pan-omics insights into abiotic stress responses: bridging functional genomics and precision crop breeding - Tayachew Admas; Shu Jiao; Rui Pan; Wenying Zhang (Functional & Integrative Genomics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Development of Palygorskite-CaIn2S4 composite for rapid Cr(VI) reduction under visible light - Yuanyuan Wang; Shijun Jia; Shiqiang Ding; Wenyan Zhang; Rui Shu; Yingfei Hu (Journal of Environmental Sciences, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Salt stress-responsive transcription factors provide insights to enhance barley improvement: a review - Tayachew Admas; Jiao Shu; Abdullah Shalmani; Rui Pan; Wenying Zhang (Planta, 2025)

Removal of disinfection residual bacteria in UV222, UV222/H2O2 and UV222/peroxymonosulfate systems: what is the safe usage for wastewater reclamation - Rui Gao; Shu-Hong Gao; Jun Li; Fang Huang; Yanmei Zhao; Jingni Xie; Yusheng Pan; Wanying Zhang; Aijie Wang (Water Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Enhanced fluoride removal through pulsed electrosorption: Optimizing energy efficiency and selectivity in complex water matrices by EDL regulation - Xun Liu; Chaoqun Zhu; Mengxia Wang; Yufei Shu; Meng Zhang; Weiwen Chen; Beizhao Chen; Siyu Cao; Rui Chen; Zhongying Wang (Chemical Engineering Journal, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

A Global Review of the Zoonotic Potential and Disease Risks of Amphibian Parasites in Bullfrog Aquaculture - Meiqi Weng; Xinhua Liu; Chenxi Zhang; Rui Shu; Andrew Wang; Haotian Zhang; Xingqiang Wang; Huirong Yang; Jinyong Zhang (Reviews in Aquaculture, 2025)
Amphibians are a diverse group of tetrapod vertebrates comprising three orders: Anura, Caudata, and Gymnophiona, which play important roles in worldwide ecosystems. Over the past 40 years, amphibian populations have sharply declined and some of them are even endangered. Specifically, it is estimated that 35 species have gone extinct, while 653 species are considered critically endangered, and 55 species are data deficient. Infectious diseases are a significant contributor to amphibian declines, with parasites being a key driving factor. A comprehensive understanding of amphibian parasites and their pathogenicity is essential for elucidating their detrimental effects on wild amphibian populations and potential risk for cultured frogs. This review summarizes the reported amphibian parasites globally, focusing on the notable pathogens that threaten the health of these populations. More than 1600 species across 19 taxa have been recorded, including 16 amoebae species, 147 apicomplexans, 86 ciliates, 52 euglena, 17 mesomycetozoans, 30 metamonads, 92 Opalinata, 11 perkinsus, 9 microsporidia, 31 myxozoans, 105 acanthocephalans, 91 cestodes, 310 trematodes, 11 monopisthocotyla, 125 polyopisthocotyla, 427 nematodes, 19 pentastomids, 11 branchiura, and 10 copepods. Their pathology and potential disease risks in bullfrog aquaculture were fully documented. Finally, their possible zoonotic risk and the potential for wild amphibian population declines are discussed. Conclusively, the consumption custom, cooking culture, increasing awareness of unscientific medical usage of frog meat and skin, and application of zoonotic parasites' transmission biology‐based healthy aquaculture models and techniques determine the extremely low zoonotic risk of edible cultured bullfrogs.

Anisotropic and isotropic gold nanomaterials continue to heat up: From properties to food safety monitoring - Rui Shu; Sijie Liu; Jianlong Wang; Daohong Zhang (Trends in Food Science & Technology, 2025)

A particle counting immunosensor for the sensitive detection of ochratoxin A via click chemistry-mediated signal amplification - Rui Chen; Yongzhen Dong; Shuhuai Li; Xionghui Ma; Chaohai Pang; Shu Wang; Jiangjiang Zhang; Yiping Chen (Journal of Hazardous Materials, 2025)

Enhancing desalination efficiency in PCM-FCDI systems through optimized interlayer channel design and flow dynamics - Rui Chen; Xun Liu; Mengxia Wang; Yufei Shu; Meng Zhang; Bei Liu; Zhongying Wang (Desalination, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Antibody-mimic nanozyme mediating sandwich lateral flow immunoassay with bulk and parallel catalysis for Salmonella typhimurium detection - Rui Shu; Sijie Liu; Meilin Wang; Xuechi Yin; Yuanyuan Cheng; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2025)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

A novel two-stage continuous capacitive deionization system with connected flow electrode and freestanding electrode - Rui Chen; Xun Liu; Mengxia Wang; Yufei Shu; Meng Zhang; Bei Liu; Zhongying Wang (Chemical Engineering Journal, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

3D gravity inversion using cycle-consistent generative adversarial network - Shu-Bo Qiao; Hou-Pu Li; Rui Qi; Yu-Jie Zhang; Shi-Min Xie (Applied Geophysics, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Fossil woods of Cryptocarya (Lauraceae) from the middle Miocene of Southwest China - Rui Zhang; Lu-Liang Huang; Shu-Feng Li; Tao Su; Alexei A. Oskolski (Review of Palaeobotany and Palynology, 2024)

Two birds with one stone: Gold “bridging” both nanozyme and immunosensor for sensitive double-response detection of T-2 toxin - Rui Shu; Sijie Liu; Cong Zhao; Xi Lan; Yuechun Li; Jianlong Wang; Nannan Qiu; Daohong Zhang (Chemical Engineering Journal, 2024)

Physiochemical and biological characteristics of fouling on landfill leachate treatment systems surface - Zhourui Gong; Shu Yang; Rui Zhang; Yangqing Wang; Xiaoqing Wu; Liyan Song (Journal of Environmental Sciences, 2024)

Long-term and short-term disposal of landslide dams at steep V-shaped valleys - Jingwen Wang; Rui Wang; Chong Zhang; Zihao Ma; Guangming Tan; Caiwen Shu; Shasha Han; Haixin Shang; Guangyue Zhang; Yizheng Zhan (Landslides, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Application of Matrigel in the 3-dimension culture of female germline stem cells - Wen Zhang; Yang Cheng; Shu Zhang; Rui Wei; Kang Zou (Reproductive Biology, 2023)

A landfill serves as a critical source of microplastic pollution and harbors diverse plastic biodegradation microbial species and enzymes: Study in large-scale landfills, China - Xiaoxing Lin; Shanshan Zhang; Shu Yang; Rui Zhang; Xianyang Shi; Liyan Song (Journal of Hazardous Materials, 2023)

Achieving reasonable waste heat utilization in all truck operating conditions via a dual-pressure organic rankine cycle and its operating strategy - Xuanang Zhang; Xuan Wang; Jinwen Cai; Rui Wang; Xingyan Bian; Ping Yuan; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2023)

Ru-catalyzed chemoselective methoxycarbonylation of methyl pentenoate: An assistant role of chloride anions - Shu Zhang; Rui Sun; Pengxin Guan; Yaofeng Wang; Ling Wang; Yanli Zhu; Lijun Han; Jiayu Xin (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Elemental Geochemical Distribution of the Jurassic Yan'an Formation in the Ningdong Coalfield and its Controlling Effect on Coal Reservoir Properties - Jincheng Ye; Yafei Zhang; Wei He; Rui Tao; Shu Tao; Shida Chen; Yi Cui; Qi Wang (Natural Resources Research, 2023)

All-in-one device for mapping the interactive effects of photodynamic therapy dosimetry in tumor gaseous microenvironment - Shu Zhang; Yuewu Li; Rui Dong; Weitao Li; Zhiyu Qian; Yamin Yang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Antibiotics and antibiotic-resistant genes in municipal solid waste landfills: Current situation and perspective - Liyan Song; Shu Yang; Zhourui Gong; Jun Wang; Xianyang Shi; Yangqing Wang; Rui Zhang; Yongchun Wu; Yongli Z. Wager (Current Opinion in Environmental Science & Health, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

High ambient temperatures are associated with urban crime risk in Chicago - Kun Hou; Liqiang Zhang; Xia Xu; Feng Yang; Baozhang Chen; Wei Hu; Rui Shu (Science of The Total Environment, 2023)

Maternal atmospheric particulate matter exposure and risk of adverse pregnancy outcomes: A meta-analysis of cohort studies - Liangliang Ju; Lei Hua; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Pollution, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Outdoor air pollution exposure and the risk of asthma and wheezing in the offspring - Lei Hua; Liangliang Ju; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Association between exposure to air pollutants and the risk of inflammatory bowel diseases visits - Siwen Ding; Shu Sun; Rui Ding; Shasha Song; Yi Cao; Lijiu Zhang (Environmental Science and Pollution Research, 2022)

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Prenatal air pollution exposure increases the risk of macrosomia: evidence from a prospective cohort study in the coastal area of China - Changlian Li; Liangliang Ju; Mei Yang; Qi Zhang; Shu Sun; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Picraquanines A－C, three new phenolic derivatives from the stems of Picrasma quassioides - Rui Xu; Dongdong Zhang; Fangfang Shu; Zehai Long; Yiming Li; Zhengtao Wang; Li Yang; Rui Wang (Natural Product Research, 2021)

Associations between air pollution exposure and birth defects: a time series analysis - Shu Sun; Qi Zhang; Xinmiao Sui; Liu Ding; Jie Liu; Mei Yang; Qihong Zhao; Chao Zhang; Jiahu Hao; Xiujun Zhang; Shilei Lin; Rui Ding; et al. (Environmental Geochemistry and Health, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Growth marks in eyestalks of Portunus trituberculatus: A development of technique and evidence of molting - Bilin Liu; Jian Zhang; Jiang Rui; Zhenyu Ni; Chang Shu (Acta Oceanologica Sinica, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

The short-term effect of PM2.5/O3 on daily mortality from 2013 to 2018 in Hefei, China - Xinmiao Sui; Junqing Zhang; Qi Zhang; Shu Sun; Ruoqian Lei; Chao Zhang; Han Cheng; Liu Ding; Rui Ding; Changchun Xiao; Xiaoru Li; Jiyu Cao (Environmental Geochemistry and Health, 2021)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

Age- and region-related response of radial growth to climate warming and a warming hiatus - Lingnan Zhang; Rui Wang; Xianfeng Liu; Yilin Ran; Shu Shang; Xiaohong Liu (Trees, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Thermal recovery process of a backfilled open-pit in permafrost area at the Gulian strip coal mine in Northeast China - Shu-hui Gao; Rui-xia He; Hui-jun Jin; Ya-dong Huang; Jian-ming Zhang; Dong-liang Luo (Journal of Mountain Science, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

MiR-28 inhibits cardiomyocyte survival through suppressing PDK1/Akt/mTOR signaling - Rui-Yao Zhu; Di Zhang; Han-Dong Zou; Xiao-Shu Zuo; Qing-Shan Zhou; He Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Screening for cold-resistant tomato under radiation mutagenesis and observation of the submicroscopic structure - Shuai Wang; Rui Yang; Chang Shu; Xichun Zhang (Acta Physiologiae Plantarum, 2016)

Nucleus accumbens hyperpolarization-activated cyclic nucleotide-gated channels modulate methamphetamine self-administration in rats - Dan-Ni Cao; Rui Song; Shu-Zhuo Zhang; Ning Wu; Jin Li (Psychopharmacology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

Reconstruction of historical lead contamination and sources in Lake Hailing, Eastern China: a Pb isotope study - Rui Zhang; Minglei Guan; Yujie Shu; Liya Shen; Xixi Chen; Fan Zhang; Tiegang Li; Tingchen Jiang (Environmental Science and Pollution Research, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Effect of the CYP2D6 gene polymorphism on postoperative analgesia of tramadol in Han nationality nephrectomy patients - Hong Dong; Shu-jun Lu; Rui Zhang; Dong-dong Liu; Yan-zhuo Zhang; Chun-yu Song (European Journal of Clinical Pharmacology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

A new alkaloid from the fruit of Nandina domestica Thunb. - Cai-Ying Peng; Jian-Qun Liu; Rui Zhang; Ji-Cheng Shu (Natural Product Research, 2014)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

ST13, a proliferation regulator, inhibits growth and migration of colorectal cancer cell lines - Rui Bai; Zhong Shi; Jia-wei Zhang; Dan Li; Yong-liang Zhu; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Changes in bacterial community of anthracene bioremediation in municipal solid waste composting soil - Shu-ying Zhang; Qing-feng Wang; Rui Wan; Shu-guang Xie (Journal of Zhejiang University-SCIENCE B, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Risk assessment of polycyclic aromatic hydrocarbons in aquatic ecosystems - Bing Wu; Rui Zhang; Shu-Pei Cheng; Timothy Ford; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Identification of novel serum biomarkers in child nephroblastoma using proteomics technology - Qian Zhang; Jiaxiang Wang; Rui Dong; Shaobo Yang; Shu Zheng (Molecular Biology Reports, 2011)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Preparation and bioevaluation of 99mTc-HYNIC-annexin B1 as a novel radioligand for apoptosis imaging - Quan-Yong Luo; Fang Wang; Zhi-Yong Zhang; Yi Zhang; Han-Kui Lu; Shu-Han Sun; Rui-Sen Zhu (Apoptosis, 2008)

Trehalose synthase gene transfer mediated byAgrobacterium tumefaciens enhances resistance to osmotic stress in sugarcane - Zi-Zhang Wang; Shu-Zhen Zhang; Ben-Peng Yang; Yang-Rui Li (Sugar Tech, 2005)